Recovery and genotyping ancient Sicilian monumental olive trees - Marchese, A.; Bonanno, F.; Marra, F. P.; Trippa, D. A.; Zelasco, S.; Rizzo, S.; Giovino, A.; Imperiale, V.; Ioppolo, A.; Sala, G.; Granata, I.; Caruso, T. (Frontiers in Conservation Science, 2023)
The long-lived and evergreen olive tree dominates the Mediterranean landscape representing an agroecological and cultural symbol and a genetic heritage of inestimable value. Sicily, for historical, geographical, and cultural reasons, has a very rich and distinctive olive germplasm. In this work, a large survey was conducted to discover, collect, and characterize the genetic diversity of centennial monumental olive trees from historical sites, such as the Greek Temple Valley (Agrigento), ancient gardens or farmland present in the western part of the island. Trees were chosen based on their height, trunk, and stump size, and presumed age, particularly only olive trees which age estimated more than 400-year-old were taken into consideration. For the morphological characterization, traits of leaf, fruit, and endocarp, were analysed. For the molecular characterization, 11 polymorphic microsatellite markers largely used for fingerprinting analysis were used. Reference cultivars were included in the analysis for comparison. Nuclear DNA was extracted from different part of the plant (young leaves of shoots taken from the canopy and young leaves taken from suckers, arose from the basal part of the tree) to check if trees were grafted and to explore their diversity. Most of the monumental trees have been grafted at least one time during their long life and some genotypes showed unique genetic profiles combined with peculiar phenotypic traits. Suckers (rootstock of the trees) showed strict genetic relationship with an ancient monumental oleaster tree, also included in the study. “Patriarch” (original mother plants) trees of local cultivars have been also identified. This research revealed a high level of still unexplored genetic diversity of the Sicilian olive germplasm and highlighted its importance as gene reservoir which could support new breeding programs for the evaluation and possible selection of traits linked to putative resilience to abiotic and biotic stresses (particularly Xylella fastidiosa subsp. pauca ST53, or soil borne diseases or insects). The results will be functional for improving the conservation process, enriching existing collections of olive genetic resources, and supporting on-farm conservation projects.